Lecturer-Informed Instructional Design Requirements for Developing a Project-Based Collaborative Learning Model toward SDG 4 - Zet Yulius Baitanu; Suryanti Suryanti; Lamijan Hadi Susarno (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To identify and prioritise lecturers’ instructional needs and translate integrated evidence into lecturer-informed design requirements for developing a Project-Based Collaborative Learning (PjBCL) model in higher education. It also examined how the resulting requirements could support SDG 4 by strengthening contextually relevant and competency-oriented quality education. Method: The study employed the Preliminary Research phase of Educational Design Research. A needs-assessment questionnaire was pilot-tested with 11 lecturers and administered to 78 lecturers at an Indonesian public university using purposive sampling. Quantitative data were analysed using descriptive statistics and internal-consistency testing, while qualitative responses were examined through inductive content analysis. The two strands were integrated using Joint Display and Meta-Inference. Results: The analysis produced four interrelated instructional design requirements: local contextualisation, authentic collaborative learning, institutional readiness, and student competency development. Local-context integration received the highest quantitative rating (M = 4.65, SD = 0.41), and qualitative findings specified the cultural, pedagogical, organisational, and partnership conditions required to operationalise these priorities. Novelty: The study advances Educational Design Research by demonstrating a transparent evidence-to-design pathway that converts lecturers’ quantitative priorities and qualitative explanations into explicit instructional design requirements before model development. This lecturer-informed process provides an empirical foundation for designing and iteratively refining a context-responsive PjBCL model aligned with SDG 4 (Quality Education).